2011
DOI: 10.5090/kjtcs.2011.44.5.348
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Traumatic Rupture of the Diaphragm

Abstract: BackgroundTraumatic rupture of the diaphragm is an unusual type of trauma. In addition, it is difficult to diagnose because it can be accompanied by injuries to other organs. If it is not detected early, the mortality rate can increase due to serious complications. Diaphragmatic rupture is an important indicator of the severity of the trauma. The aim of this study was to investigate the factors affecting the incidence of complications and mortality in patients who had surgery to treat traumatic rupture of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 15 publications
1
19
0
9
Order By: Relevance
“…Magnetic resonance imaging can be a good diagnostic tool, but it cannot be performed in an emergency setting. [21] Oral follow-through study was performed in two patients, and it revealed positive results; chest X-ray results in both these patients were negative. The patients with SDR demonstrated negative results on chest X-ray, chest CT, upper gastrointestinal endoscopy, and abdominal USG before being diagnosed using oral follow-through.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Magnetic resonance imaging can be a good diagnostic tool, but it cannot be performed in an emergency setting. [21] Oral follow-through study was performed in two patients, and it revealed positive results; chest X-ray results in both these patients were negative. The patients with SDR demonstrated negative results on chest X-ray, chest CT, upper gastrointestinal endoscopy, and abdominal USG before being diagnosed using oral follow-through.…”
Section: Discussionmentioning
confidence: 94%
“…[18,20] Furthermore, sensitivity of CT in diagnosing acute DR ranges between 33% and 83%, and its specificity ranges between 76% and 100%. [18,21] CT findings in acute DR are hemidiaphragmatic discontinuity, intrathoracic herniation of the abdominal content, and the dependent viscera sign. [22,23] In our series, CT revealed a DR in three of five stable polytraumatized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Diyafragma hernilerinin tedavisi cerrahidir. Cerrahide torakotomi, laparotomi veya her iki yaklaşımın aynı ayda uygulanması gerektiğini savunan çalışmalar mevcuttur [6,7]. Bununla beraber torakoabdominal yaklaşımın en ideal cerrahi yaklaşım olduğu görüşünde olanlar da vardır [8].…”
Section: Editör Içinunclassified
“…Anahtar Kelimeler: Travmatik diyafragma hernisi, anestezi, genel, oksijen, azot protoksit Özet / Abstract Giriş D iyafragma, en önemli solunum kasıdır (1). Diyafragma üzerinde bir defekt sonucu ortaya çıkan diyafragma hernileri, kalıtsal veya kazanılmış olabilirler.…”
unclassified